PREVALENCE OF LEARNING DISORDER AMONG STUDENTS OF SOCIO-ECONOMICALLY DISADVANTAGED FAMILY IN MANIKANDAM BLOCK OF TIRUCHIRAPPALLI DISTRICT- A DESCRIPTIVE STUDY - Mary, Lourdu; Indhumathi, R. (International Journal of Psychosocial Rehabilitation, 2020)
Various research studies have proved that Disability is generally more common among children living in poverty than among those not living in poverty. In the education system, the disproportionate recognition of learning disorders in such socio demographic groups, especially, the already disadvantaged group is viewed as a chronic issue. Students who are misidentified with a learning disorder may be extremely limited in their academic and social environments, while the students with a learning disorder who are never identified are less likely to obtain the adaptations and modifications required to explore out their full potential. Therefore, the poverty and learning disorders can decrease the likelihood of completing the high school education which is considered as great barrier in breaking the intergenerational cycle of poverty. Aim: The main aim of the present study is to understand the different type of learning disorder among students of socio-economically disadvantaged family. The objectives of the study are: to describe the socio-demographic characteristic of the respondents, to identify the different type of learning disorder among students of socio-economically disadvantaged family. descriptive research design has been adopted. The universe of the study consists of students of socio-economically disadvantaged family in Manikandam block of Tiruchirappalli district. There are about 190 sample were selected. The module NIMHAANS index for specific learning disabilities ( modified version) has been adopted to identify the various learning disorder. More than half (51.0 percent) of the students of socio-economically disadvantaged family are identified with different types of Learning Disorders so they should be given appropriated intervention by psychologist in order to overcome the leaning disorder of the students of socio-economically disadvantaged family.